Morphological asymmetry and broiler welfare - Nääs,IA (2008)
Health status, feed conversion ratio, and mortality are long known broiler chicken production indicators. However, further parameters are required by today's demanding meat markets, as these indicators are not sufficiently accurate to determine flock overall welfare. Morphological asymmetry has been pointed as an alternative welfare indicator as it reflects the ability of the bird to cope with the challenges that rearing conditions may impose. This study aimed at evaluating the possibility of using morphological asymmetry as a welfare indicator. Broilers from 28 to 42 days of age were used in the trial. Birds were randomly selected in a commercial poultry farm and transported to the laboratory. They walked over the force measurement platform in order to determined their feet force as a percentage of body weight. The following body parts of the live birds were measured by two different operators using a digital caliper: tarsometatarsus length, outertoe length, midtoe length, and backtoe length. In the corresponding carcasses, the following traits were measured: wattle width, eye length, and first secondary feather length. Data were submitted to statistical analyses and no correlation was found between specific feet trait measurements and walking ability. Considering the time budget involved in measuring morphological asymmetry, this procedure did not appear to be a practically feasible welfare indicator.